Effects of short term vocational trainings on income distribution among young people in rural Zimbabwe - Sibanda, Simbarashe (My University, 2021)
Youth unemployment remains a global challenge. Increasingly, improving access to skills for employability is seen as a viable policy options to deal with this issue with expanding access to technical and vocational education and training being the preferred option. There have been several examples of such efforts across the African continent. In Zimbabwe, one such programme was designed to deliver short-term vocational skills training targeting young people in the rural informal economy. This study sought to analyse the effectiveness of this intervention. Firstly, the study explored the relationship between educational attainment and income for young people working in the rural informal economy. It examined the effect of introducing a short term technical vocational training programme on the relationship between educational attainment and incomes. Lastly, the study investigated how the introduction of targeted short training affects income inequality among workers in the informal economy.The study, a secondary analysis, employed a descriptive relational correlation approach. The study reconfirmed the primary findings, that skills training led to significant increases in incomes for the population. However, the impact of the intervention was different across the different subpopulations. The increase in incomes was disproportionate, with a small proportion of young people realizing astronomical increases in incomes. The secondary analysis found that level of educational attainment as a variable is a poor predictor of income level. This remained true even after the skills training, suggesting that the human capital theory may not be highly applicable in a highly informal rural economy similar to Zimbabwe. Lastly, the intervention had a positive but negligible impact on reducing income inequality
A research report submitted to the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Education, School of Education